KEPEMIMPINAN GURU PENDIDIKAN ANAK USIA DINI DALAM MENANAMKAN KARAKTER PERSPEKTIF AL-QUR'AN - Aziz, Mursal; Ashshiddiqi, Muhammad Hasbie; Rosidah, Rosidah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Early Childhood Education (PAUD) has a fundamental role in the formation of children's character which will later influence their behavior and morals in the future. Teacher leadership in PAUD is not only limited to teaching, but also includes the role as a guide to children's character. This article aims to examine the leadership of PAUD teachers in instilling character values ​​in children, with an approach based on the perspective of the Qur'an. Using a library research method, this article analyzes the texts of the Qur'an that are relevant to the principles of leadership, as well as the application of these values ​​in the context of early childhood education. The novelty of this study lies in the perspective of the in-depth application of the Qur'an in the map of ideal leadership characteristics for PAUD teachers, including the values ​​of honesty, compassion, discipline, and justice. The results of this study found that from the perspective of the Qur'an, a teacher's leadership must include exemplary behavior, wisdom, and patience, all of which play a role in forming children's character in a gentle and understanding manner. This study also suggests that the application of these principles in teaching practice can optimize the process of forming children's character and strengthen children's moral foundations from an early age. Through this literature research, it is hoped that it can provide a contribution to the development of educational practices based on the spiritual values ​​contained in the Al-Quran.